Transgenic Schwann cells overexpressing POU6F1 promote sciatic nerve regeneration within acellular nerve allografts. (1st December 2022) - Li, Wen-Yuan; Li, Zhi-Gang; Fu, Xiu-Mei; Wang, Xiao-yu; Lv, Zhong-xiao; Sun, Ping; Zhu, Xiao-Feng; Wang, Ying
Abstract: Objective. Acellular nerve allograft (ANA) is an effective surgical approach used to bridge the sciatic nerve gap. The molecular regulators of post-surgical recovery are not well-known. Here, we explored the effect of transgenic Schwann cells (SCs) overexpressing POU domain class 6, transcription factor 1 (POU6F1) on sciatic nerve regeneration within ANAs. We explored the functions of POU6F1 in nerve regeneration by using a cell model of H2 O2 -induced SCs injury and transplanting SCs overexpressing POU6F1 into ANA to repair sciatic nerve gaps. Approach. Using RNA-seq, Protein–Protein Interaction network analysis, gene ontology enrichment, and Kyoto Encyclopedia of Genes and Genomes pathway analysis, we identified a highly and differentially expressed transcription factor, POU6F1, following ANA treatment of sciatic nerve gap. Expressing a high degree of connectivity, POU6F1 was predicted to play a role in peripheral nervous system myelination. Main results. To test the role of POU6F1 in nerve regeneration after ANA, we infected SCs with adeno-associated virus—POU6F1, demonstrating that POU6F1 overexpression promotes proliferation, anti-apoptosis, and migration of SCs in vitro . We also found that POU6F1 significantly upregulated JNK1/2 and c-Jun phosphorylation and that selective JNK1/2 inhibition attenuated the effects of POU6F1 on proliferation, survival, migration, and JNK1/2 and c-Jun phosphorylation. The direct interaction of POU6F1 and activated JNK1/2 was subsequently confirmed by co-immunoprecipitation. In rat sciatic nerve injury model with a 10 mm gap, we confirmed the pattern of POU6F1 upregulation and co-localization with transplanted SCs. ANAs loaded with POU6F1-overexpressing SCs demonstrated the enhanced survival of transplanted SCs, axonal regeneration, myelination, and functional motor recovery compared to the ANA group loaded by SCs-only in line with in vitro findings. Significance. This study identifies POU6F1 as a novel regulator of post-injury sciatic nerve repair, acting through JNK/c-Jun signaling in SCs to optimize therapeutic outcomes in the ANA surgical approach.